Compact Wideband Antiparallel Diode Frequency Triplers Utilizing Planar Transitions - Wahab Mohyuddin; Kang Wook Kim; Hyun Chul Choi (International Journal of Antennas and Propagation)
Two designs of frequency triplers, which use planar transitions as baluns and an antiparallel diode pair to achieve wide bandwidth, are presented. The ultrawideband transitions are utilized for input and output impedance matching of the frequency triplers. The design process and operation principles are described in this paper. The implemented frequency triplers exhibit flat response over wide frequency range of 3 to 9 GHz. The proposed Type A frequency tripler shows conversion loss of ~18 dB with above 30 dB even harmonics suppression. With Type B frequency tripler, conversion loss of ~17 dB and above 25 dB even harmonic suppression are achieved.